Household willingness to pay for mandated kerbside recycling programme in Hulu Langat, Malaysia - Ng, Phuay Ying (2011)
The aim of this study is to determine contingent valuation (CV) estimates of household willingness to pay (WTP) to a mandated kerbside recycling program (KRP) through time-use approach in two separate aspects; the opportunity costs of time used for waste self-sorting and WTP for others to do the sorting. Specifically, the purpose of this research was to ascertain how much people would be willing to pay for an environmentally sound waste management without any effort or work on their behalf. Furthermore, to determine residents' attitudes and behaviour towards recycling, factors influencing recycling behaviour before and after proposed idea of KRP. Finally, to examine to what extent various attitudinal, behavioural, and demographic variables were associated with WTP served as another specific aim. An open-ended iterative bidding WTP question was applied, the scale of the bid levels being established from a pilot sample of respondents presented with an open ended WTP question. Survey data was gathered and conducted within the District of Hulu Langat, Selangor involving samples of 250 families. The study was unique in that, as the programme was already implemented in few cities in Malaysia, the respondents had relatively a higher level of information about the commodity that they were valuing; therefore, biasness of CV studies can be reduced. The survey was accessed together with some recycling questions, yielding responses to be correlated to the utility that individuals were assembling of the recycling activities. Based on the regression analysis, the WTP was influenced by socio-demographic factors (education, age and whether an individual a recycler or not). If the programme was mandated, the value of WTP would be higher. Furthermore, the mean WTP for mandated KRP is estimated to be RM5.45 per household. This value is not just an amount that people would pay to have the sorting service; it somehow enlighten the expected worth of the service.